2015
DOI: 10.1080/10106049.2014.978903
|View full text |Cite
|
Sign up to set email alerts
|

GIS based drainage morphometry and its influence on hydrology inparts ofWestern Ghats region, Maharashtra, India

Abstract: A c c e p t e d M a n u s c r i p t RESEARCH ARTICLEGIS based drainage morphometry and its influence on hydrology in parts of Western Ghats region, Maharashtra, IndiaVarious drainage morphometric parameters in the Upper Bhima river basin and its influence on hydrological processes (e.g runoff, peak flow, time to peak, infiltration, overland flow etc.) were discussed using Geographical Information System (GIS) and Remote Sensing (RS) techniques. Survey of India (SoI) topographical maps and ASTER Digital Elevati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 39 publications
0
29
0
1
Order By: Relevance
“…The western margin the basin is highly rugged due to presence of Western Ghats which gradually merges towards basin outlet. Due to natural barrier, the western part of the basin receives more than 3000 mm of rainfall and decreases towards east [Samal and Gedam, 2015]. Heavy rainfall in Ghats region leads to construction of several reservoirs for storing water and use it during non-monsoon months.…”
Section: Study Areamentioning
confidence: 99%
“…The western margin the basin is highly rugged due to presence of Western Ghats which gradually merges towards basin outlet. Due to natural barrier, the western part of the basin receives more than 3000 mm of rainfall and decreases towards east [Samal and Gedam, 2015]. Heavy rainfall in Ghats region leads to construction of several reservoirs for storing water and use it during non-monsoon months.…”
Section: Study Areamentioning
confidence: 99%
“…The peripheral areas of sub-watersheds in present study show steep slopes where first and second order streams are concentrated ( Figure 5). High average slopes in sub-watershed 1 is ranked 14 with increased stream flow velocity, minimized length of overland flow and quick water flow into streams contributing to hydrograph rise (Samal et al 2015). It has been observed that subwatershed 12 has low average slopes and therefore ranked 1 (Table 2) shows less runoff, relatively less land erosion and low peaks in hydrograph.…”
Section: Relief Aspectsmentioning
confidence: 99%
“…Basin relief is a key indicator of a drainage system shown by the elevation (Samal et al 2015). The 'Rhl' is the ratio between the total relief and the lengthiest measurement of the basin parallel to the main drainage line (Schumm 1956) and it is directly related to the 'Lg' and time to peak.…”
Section: Relief Characteristics Of the Kosi Basinmentioning
confidence: 99%
“…High 'C' value in any basin displays the basin area of lower stream order drainages are fairly larger than the sub-basins which have lower C value. Low 'C' value in the basin reduces length of overland flow (Lg), thus water discharges rapidly as channel flow in scant vegetation cover (Samal et al 2015).…”
Section: Drainage Texture (Dt)mentioning
confidence: 99%
See 1 more Smart Citation